2015
DOI: 10.1039/c5ra04442a
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and in vivo chondrification of a poly(propylene carbonate)/l-lactide-grafted tetracalcium phosphate electrospun scaffold for cartilage tissue engineering

Abstract: Regenerative therapies that utilize stem cell differentiation in three-dimensional porous scaffolds have attracted significant interest in recent years. In this study, fibrous poly(propylene carbonate)/poly(L-lactic acid)-grafted tetracalcium phosphate (PPC/g-TTCP) scaffolds were prepared using an electrospinning method. The characteristics of the fabricated scaffolds were investigated using scanning electron microscopy, differential scanning calorimetry, thermogravimetric analyses, Fourier transform infrared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Derivatives based on 9, 10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide (DOPO) is an attractive FR. It has been reported that the DOPO‐based FRs are effective for epoxy resins , polyurethane foams , polylactic acid (PLA) , and polyamide 6 . Because the condensed phase formed in the combustion process can prevent heat and mass transfer profited from the addition of phenethyl‐bridged DOPO derivative (DiDOPO) , it can prevent heat and mass transfer profited from the addition of DiDOPO, which plays an important role in radical quenching mechanism .…”
Section: Introductionmentioning
confidence: 99%
“…Derivatives based on 9, 10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide (DOPO) is an attractive FR. It has been reported that the DOPO‐based FRs are effective for epoxy resins , polyurethane foams , polylactic acid (PLA) , and polyamide 6 . Because the condensed phase formed in the combustion process can prevent heat and mass transfer profited from the addition of phenethyl‐bridged DOPO derivative (DiDOPO) , it can prevent heat and mass transfer profited from the addition of DiDOPO, which plays an important role in radical quenching mechanism .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In recent years, there has been an increasing growth in the use of long glass-fibre–reinforced thermoplastic composites for semi-structural and engineering applications, caused by the fact that the composites show advantages of being lightweight and cost-effective as well as demonstrate high mechanical strength and excellent rigidity; these attractive advantages make them suitable for applications in automobiles, construction and aviation fields. 4 –9 In addition, as compared to ordinary PP composites, the long glass-fibre–reinforced PP (PP/LGF) composites are more suitable for applications that necessitate high demands.…”
Section: Introductionmentioning
confidence: 99%
“…The fabricated fibrous mats exhibited a Young's modulus similar to that of human arteries (0.4–0.8 MPa) . Moreover, using the same method, Deng et al prepared PPC/poly l ‐lactic acid‐grafted tetracalcium phosphate (PPC/g‐TTCP) scaffolds that could be used for cartilage defect repair. Fan et al developed a microcavitary hydrogel (MCG) with photopolymerization of biodegradable oligo(TMC)‐PEG‐oligo(TMC) diacrylate macromer, in which cavities with hundreds of microns in diameter were created using gelatin microspherical porogens.…”
Section: Applicationsmentioning
confidence: 99%